Adsorptive removal of dyes from aqueous solution onto carbon nanotubes: A review - Gupta, Vinod Kumar; Kumar, Rajeev; Nayak, Arunima; Saleh, Tawfik A.; Barakat, M.A. (Advances in colloid and interface science, 2013)
Adsorption is a widely used technique for the separation and removal of pollutants from wastewaters. Carbon nanotubes (CNTs) are emerging as potential adsorbents because of its well defined cylindrical hollow structure, large surface area, high aspect ratios, hydrophobic wall and easily modified surfaces. In this review, dye adsorption capability of CNTs and CNT based composites from aqueous system has been compiled. This article provides the information about the defect, adsorption sites on CNTs and batch adsorption studies under the influence of various operational parameters such as contact time, solution pH, temperatures etc. and deals with mechanisms involved in adsorption of dyes onto CNTs. From the literature reviewed, it is observed that single walled carbon nanotubes (SWCNTs) show higher adsorption capacity than multi walled carbon nanotubes (MWCNTs) and functionalized and CNT composite have better sorption capacity than as grown CNTs. It is evident from the literature that CNT based nanosorbents have shown good potential for the removal of dyes from aqueous solution. However, still more research work should be focused on the development of cost effective, higher efficient and environmental friendly CNT based nanosorbents for their commercial applications. [Display omitted] •Adsorption of dyes onto CNTS and CNT based composite adsorbents has been reviewed.•Adsorption of dyes onto CNTS is highly dependent on solution pH, concentration and temperature.•The sorption capacities of MWCNTs for dyes are lower than SWCNTs.•π–π interaction and electrostatic interactions are mainly involved in the adsorption.